Autonomy Markers in Brazilian Adults With Intellectual Disabilities - Santos, Flávia Heloísa dos [UNESP]; Groth, Silvana Maria; Machado, Maria Luiza (John Wiley & Sons Inc, 2009)
The objective of the study was to investigate the relationship between autonomy markers in adult people with intellectual disabilities (ID) and variables such as intelligence quotient (IQ), early aging, and literacy. Participants were 47 adults with ID (33 men; aged 28-58 years with nonspecific etiology, 34 literate). All participants were trainees at the Center for Training of Capacity and Orientation for Employment at Associação de Pais e Amigos dos Excepcionais de São Paulo, São Paulo State, Brazil. They were divided into two age groups: younger (n = 27, mean age 31.85; +/- 2.23), and older (n = 38, mean age 41.84; +/- 5.54). They were administered intelligence scales twice, and answered questions related to social participation, community integration, and choice-making; the percentage of item responses leaning toward self-determination and freedom in choice-making was considered in defining the autonomy score. For both groups, IQ declined from the first to the second assessment. Autonomy scores were more determined by IQ classification than by literacy. Authors concluded that autonomy in people with ID is a multifactorial phenomenon associated with cognitive decline.
Keywords: autonomy; choice making; cognitive decline; dementia; intellectual disabilities